Nanotube material, modified electrode, electrochemical sensor and application thereof

By using a covalent organic frame to coat carbon nanotube materials (COFs@MWCNTs) in electrochemical sensors, the problem of heavy metal lead detection in electronic cigarettes is solved, and the detection effect of high sensitivity and low detection limit is achieved.

CN119797339APending Publication Date: 2025-04-11YUNNAN TOBACCO QUALITY SUPERVISION MONITORING STATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878107.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has problems such as time-consuming, expensive equipment and complex operation in the detection of heavy metal lead in electronic cigarettes, making it difficult to achieve simple and efficient detection.

Method used

The covalent organic frame-coated carbon nanotube materials (COFs@MWCNTs) were synthesized through solvothermal reaction, and integrated into an electrochemical sensor, and the square wave anode dissolution voltammetry was used to achieve accurate detection of Pb2+.

Benefits of technology

Low detection limit (0.0749μg/L) and high sensitivity (0.221μA/(μg/L) detection of Pb2+ were achieved, and the sensor showed good repeatability, reproducibility and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797339A_ABST
    Figure CN119797339A_ABST
Patent Text Reader

Abstract

The invention discloses a nanotube material, a modified electrode, an electrochemical sensor and application of the nanotube material, a covalent organic framework coated carbon nanotube material is synthesized by using a multi-walled carbon nanotube, 5, 5 '-diamino-2, 2' dipyridyl and 2, 4, 6-triformyl phloroglucinol through solvothermal reaction. The prepared material is only composed of C, N and O, and has a tubular structure. COFs (at) MWCNTs are integrated into a novel electrochemical sensor, and accurate detection of Pb < 2 + > in an actual sample is realized through square wave anodic stripping voltammetry. When the COFs (at) MWCNTs electrochemical sensor is used for detecting Pb < 2 + >, the Pb < 2 + > detection limit of the sensor reaches 0.0749 [mu] g / L level, the sensitivity is 0.221 [mu] A / ([mu] g / L), and the electrochemical sensor shows excellent repeatability, reproducibility and stability in a performance test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heavy metal element detection, and in particular to a nanotube material, a modified electrode, an electrochemical sensor and applications thereof. Background Art

[0003] At present, the detection of heavy metal lead in e-cigarettes at home and abroad mainly uses methods such as inductively coupled plasma mass spectrometry (ICP-MS), synchrotron radiation X-ray spectroscopy (SR-XRF) and flame atomic absorption spectrometry (FAAS). These methods have high precision and low detection limits and play an irreplaceable role in analyzing trace heavy metals. However, they are time-consuming and require specialized technicians, expensive equipment, complex pretreatment and high maintenance costs. Therefore, only research institutions or companies that test a large number of samples will use these methods. Therefore, how to detect heavy metal elements more easily has become a technical problem that needs to be solved urgently by technicians in this field. Summary of the Invention

[0004] The present invention provides a nanotube material, modified electrode, electrochemical sensor, and its application. The present invention uses multi-walled carbon nanotubes, 5,5′-diamino-2,2′-bipyridine, and 2,4,6-triformylphloroglucinol to synthesize a covalent organic framework-coated carbon nanotube material through a solvothermal reaction. The prepared material consists only of C, N, and O and has a tubular structure. COFs@MWCNTs are integrated into a novel electrochemical sensor, and square-wave anodic stripping voltammetry is used to detect Pb in actual samples. 2+ Accurate detection of Pb using COFs@MWCNTs electrochemical sensor 2+ , the sensor is Pb 2+ The detection limit reached 0.0749 μg / L, with a sensitivity of 0.221 μA / (μg / L). In addition, the synthesized COFs@MWCNTs electrochemical sensor has good conductivity and a large number of binding sites. The electrochemical sensor showed excellent repeatability, reproducibility and stability in performance tests.

[0005] The present invention provides a nanotube material, and the preparation method thereof comprises:

[0006] Step (1.1): subjecting the solvent of 1,4-dioxane and mesitylene and the multi-walled carbon nanotubes to a first ultrasonic treatment;

[0007] Step (1.2): adding 5,5'-diamino-2,2'-bipyridine to the material obtained after the first ultrasonic treatment and continuing the second ultrasonic treatment;

[0008] Step (1.3): adding 2,4,6-triformylphloroglucinol and acetic acid to the substance obtained after the second ultrasonic treatment, and performing a third ultrasonic treatment;

[0009] Step (1.4): The material after the third ultrasonic treatment is subjected to a three-step cold-freeze-thaw cycle for multiple times;

[0010] Step (1.5): subjecting the product in step (1.4) to a solvothermal reaction under vacuum conditions;

[0011] Step (1.6): After the product in step (1.5) is cooled to room temperature, it is taken out, washed with different solvents, filtered, and vacuum dried;

[0012] Step (1.7): After the product in step (1.6) is dried, it is washed and vacuum-dried again to obtain a covalent organic framework material-coated carbon nanotube material.

[0013] In some embodiments, the volume ratio of 1,4-dioxane to mesitylene is 1:1; the mass ratio of the multi-walled carbon nanotubes to 2,4,6-triformylphloroglucinol is 1:1.

[0014] In some embodiments, the mass ratio of the 5,5'-diamino-2,2'-bipyridine to 2,4,6-triformylphloroglucinol is 3:4.

[0015] In some embodiments, the mass ratio of the 2,4,6-triformylphloroglucinol to 5,5'-diamino-2,2'-bipyridine is 4:3, and the volume ratio of the acetic acid to 1,4-dioxane is 2:1.

[0016] In some embodiments, the three-step cold-freeze-thaw method comprises: freezing the material after the third ultrasonic treatment in step (1.3) in liquid nitrogen until completely solidified, evacuating the material under a vacuum pump with a vacuum degree of -0.5 to 0 MPa, thawing the material in a water bath at 25°C to 45°C and filling it with nitrogen.

[0017] The present invention also provides a nanotube material, the preparation method of which includes:

[0018] Step (2.1): Stirring a solvent of 1,4-dioxane and mesitylene and 5,5'-diamino-2,2'-bipyridine;

[0019] Step (2.2): adding multi-walled carbon nanotubes to the product of step (2.1) and performing ultrasonic treatment;

[0020] Step (2.3): adding 2,4,6-triformylphloroglucinol and acetic acid to the substance obtained after ultrasonic treatment and stirring;

[0021] Step (2.4): The product of step (2.3) is subjected to a three-step cycle of cold-freeze-thaw multiple times;

[0022] Step (2.5): subjecting the product in step (2.4) to a solvothermal reaction;

[0023] Step (2.6): After the product in step (2.5) is cooled to room temperature, it is taken out, washed with different solvents, filtered, and vacuum dried;

[0024] Step (2.7): After the product in step (2.6) is dried, it is washed and vacuum-dried again to obtain a covalent organic framework material-coated carbon nanotube material.

[0025] The present invention also provides a modified electrode, the preparation method of which includes:

[0026] Step (3.1): sequentially polishing the surface of the glassy carbon electrode with Al2O3 slurry in descending order of particle size until the surface of the glassy carbon electrode has a mirror effect;

[0027] Step (3.2): ultrasonically clean the glassy carbon electrode polished in step (3.1) in water and then in anhydrous ethanol, and then blow dry in a protective atmosphere;

[0028] Step (3.3): evenly drop-coat the perfluorosulfonic acid resin dispersion of the covalent organic framework material-coated carbon nanotube material on the surface of the glassy carbon electrode dried in step (3.2), and air-dry naturally to obtain the covalent organic framework material-coated carbon nanotube material modified electrode.

[0029] The embodiment of the present application also provides an electrochemical sensor, comprising the modified electrode.

[0030] An embodiment of the present application further provides an application of an electrochemical sensor, wherein the electrochemical sensor is used for detecting heavy metal lead.

[0031] In some embodiments, the application method comprises:

[0032] Step (4.1): drawing a standard curve, the drawing of the standard curve comprising: adding a lead standard solution dropwise to the electrolyte according to a lead ion concentration gradient in the range of 0.1 μg / L to 200 μg / L in the electrolyte, and establishing a standard curve of lead ion concentration and peak current using an electrochemical sensor and square wave anodic stripping voltammetry; wherein, if the sample to be tested is an acidic lead-containing sample solution, the pH value of the electrolyte is adjusted to 3.5-5.5 before establishing the standard curve of lead ion concentration and peak current;

[0033] Step (4.2): Detecting the lead ion content in the sample to be tested, the detection of the lead ion content in the sample to be tested comprises: adding the sample to be tested into an electrolytic cell, and using an electrochemical sensor to detect the lead ion content in the sample to be tested using square wave anodic stripping voltammetry.

[0034] The present invention provides a nanotube material, modified electrode, electrochemical sensor, and application thereof. This application uses multi-walled carbon nanotubes, 5,5'-diamino-2,2'-bipyridine, and 2,4,6-triformylphloroglucinol to synthesize a covalent organic framework-coated carbon nanotube material via a solvothermal reaction. The prepared material consists solely of carbon, nitrogen, and oxygen and has a tubular structure. The COFs@MWCNTs are integrated into a novel electrochemical sensor, and square-wave anodic stripping voltammetry is used to detect the presence of Pb in actual samples. 2+ Accurate detection of Pb using COFs@MWCNTs electrochemical sensor 2+ , the sensor is Pb 2+ The detection limit reached 0.0749 μg / L, with a sensitivity of 0.221 μA / (μg / L). In addition, the synthesized COFs@MWCNTs electrochemical sensor has good conductivity and a large number of binding sites. The electrochemical sensor showed excellent repeatability, reproducibility and stability in performance tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The morphology and mapping (element distribution mapping) of COFs@MWCNTs in the examples of this application are shown;

[0036] Figure 2 The full XPS spectrum, high-resolution spectra of carbon and nitrogen elements, and Fourier transform infrared spectrum of COFs@MWCNTs in the examples of this application are shown;

[0037] Figure 3 In the embodiment of this application, in 0.1 mol / L acetic acid-sodium acetate aqueous solution (pH=4), the COFs@MWCNTs modified electrode reacts with different concentrations of Pd 2+ Response curve and working curve of square wave anodic stripping voltammetry with concentrations of 0.1 to 200 μg / L;

[0038] Figure 4 Pb in the electronic cigarette in the embodiment of this application 2+ Schematic diagram of the concentration. DETAILED DESCRIPTION

[0039] In order to better understand the above technical solution, the technical solution of this application is described in detail below through specific implementation methods.

[0040] In order to solve the above technical problems, an embodiment of the present application provides a nanotube material (i.e., a covalent organic framework material-coated carbon nanotube material, also referred to as COFs@MWCNTs material), the preparation method of which includes steps (1.1) to (1.7).

[0041] Step (1.1): subjecting the solvent of 1,4-dioxane and mesitylene and the multi-walled carbon nanotubes to a first ultrasonic treatment for 25-30 minutes;

[0042] Specifically, 1,4-dioxane and mesitylene solvents are placed in a vacuumable Schlenk bottle (solvent storage bottle) or ampoule, and then the multi-walled carbon nanotubes are added to the Schlenk bottle for a first ultrasonic treatment for 25-30 minutes.

[0043] In some embodiments, the volume ratio of 1,4-dioxane to mesitylene is 1: 1. In one example, the amount of 1,4-dioxane and mesitylene is 1 ml.

[0044] In some embodiments, the mass ratio of the multi-walled carbon nanotubes to 2,4,6-triformylphloroglucinol is 1: 1. In one example, the amount of the multi-walled carbon nanotubes is 20 mg.

[0045] Step (1.2): Add 5,5'-diamino-2,2'-bipyridine to the material obtained after the first ultrasonic treatment and continue the second ultrasonic treatment for 10 min-20 min;

[0046] Specifically, 5,5'-diamino-2,2'-bipyridine was added to the material after the first ultrasonic treatment in the Schlenk flask in step (1.1) and the second ultrasonic treatment was continued for 10 min-20 min.

[0047] In some embodiments, the first ultrasonic treatment has a frequency of 30-50 kHz and a power of 200-300 W.

[0048] In some embodiments, the mass ratio of the 5,5'-diamino-2,2'-bipyridine to 2,4,6-triformylphloroglucinol is 3:4. In one example, the amount of the 5,5'-diamino-2,2'-bipyridine used is 26.57 mg.

[0049] Step (1.3): adding 2,4,6-triformylphloroglucinol and acetic acid to the material obtained after the second ultrasonic treatment, and performing a third ultrasonic treatment for 10 min to 20 min;

[0050] Specifically, 2,4,6-triformylphloroglucinol and acetic acid are added to the material obtained after the second ultrasonic treatment in the schlenk flask in step (1.2) and ultrasonicated for a third time for 10 min to 20 min.

[0051] In some embodiments, the mass ratio of the 2,4,6-triformylphloroglucinol to 5,5'-diamino-2,2'-bipyridine is 4:3. In one example, the amount of the 2,4,6-triformylphloroglucinol is 20 mg.

[0052] In some embodiments, the volume ratio of the acetic acid to 1,4-dioxane is 2: 1. In one example, the acetic acid is 6M acetic acid, and the amount of 6M acetic acid used is 2 ml.

[0053] Step (1.4): the material after the third ultrasonic treatment is subjected to a three-step cold-freeze-thaw cycle 2 to 6 times;

[0054] Specifically, the material in the Schlenk flask in step (1.3) is subjected to a three-step cooling-freezing-thawing cycle 2 to 6 times.

[0055] In some embodiments, the three-step cold-freeze-thaw method comprises: freezing the material after the third ultrasonic treatment in step (1.3) in liquid nitrogen until completely solidified, evacuating the material under a vacuum pump with a vacuum degree of -0.5 to 0 MPa, thawing the material in a water bath at 25°C to 45°C and filling it with nitrogen.

[0056] Step (1.5): The product in step (1.4) is subjected to a solvothermal reaction at 110°C-130°C under vacuum conditions for 72 hours-96 hours.

[0057] In some embodiments, the vacuum condition in step (1.5) is achieved by evacuating or filling with an inert gas.

[0058] Step (1.6): After the product in step (1.5) is cooled to room temperature, it is taken out, washed with different solvents, filtered, and vacuum dried for 12 hours to 36 hours.

[0059] In some embodiments, the different solvents in step (1.6) include deionized water, methanol and ethanol.

[0060] Step (1.7): After the product in step (1.6) is dried, it is washed for 12 hours to 36 hours, and then vacuum-dried again for 12 hours to 36 hours to obtain a covalent organic framework material-coated carbon nanotube material.

[0061] Specifically, after the product in step (1.6) is dried, it is washed with a Soxhlet extractor for 12 hours to 36 hours, and then vacuum-dried again for 12 hours to 36 hours.

[0062] In some embodiments, tetrahydrofuran solvent is used for washing in step (1.7). In one example, 70 ml of tetrahydrofuran solvent is added to a 100 ml Soxhlet extractor for washing.

[0063] In the examples of the present application, the prepared COFs@MWCNTs material has a tubular structure, which is modified on a glassy carbon electrode for the detection of heavy metal lead.

[0064] In the examples of this application, the synthesized COFs@MWCNTs have good conductivity and a large number of binding sites. In addition, the COFs@MWCNTs sensor showed excellent repeatability, reproducibility and stability in the performance test. 2+ It has good electrochemical response, showing advantages such as high sensitivity, low background current and high selectivity. 2+ The detection limit reached 0.0749 μg / L, and the average recovery rate was 102.28-106.75%, showing a higher sensitivity of 0.221 μA / (μg / L) than the existing technology, indicating that the COFs@MWCNTs modified electrode provides a new path for the rapid detection of trace heavy metal ions in e-cigarette liquid.

[0065] The present embodiment also provides another nanotube material, the preparation method of which includes steps (2.1) to (2.7).

[0066] Step (2.1): Stirring a solvent of 1,4-dioxane, mesitylene, and 5,5'-diamino-2,2'-bipyridine for 15-30 minutes;

[0067] In this embodiment, the amount of raw materials used in step (2.1) can refer to the amount of the same raw materials used in step (1.1) and step (1.2).

[0068] Step (2.2): adding multi-walled carbon nanotubes to the product of step (2.1) and ultrasonically treating for 20 min to 35 min;

[0069] In this embodiment, the amount of multi-walled carbon nanotubes used can refer to the amount of the same raw materials used in step (1.1).

[0070] Step (2.3): adding 2,4,6-triformylphloroglucinol and acetic acid to the material obtained after ultrasonic treatment, and stirring for 20 min to 35 min;

[0071] In this embodiment, the amounts of 2,4,6-triformylphloroglucinol and acetic acid can refer to the amounts of the same raw materials in step (1.3).

[0072] Step (2.4): The product of step (2.3) is subjected to a three-step cycle of cold-freeze-thaw 2 to 6 times;

[0073] In this embodiment, the three-step cold-freeze-thaw method in step (2.4) can refer to the specific setting method and parameters of the three-step cold-freeze-thaw method mentioned above.

[0074] Step (2.5): subjecting the product of step (2.4) to a solvothermal reaction at 110° C.-150° C. for 60 h-96 h;

[0075] Step (2.6): After the product in step (2.5) is cooled to room temperature, it is taken out, washed with different solvents, filtered, and vacuum dried for 12 hours to 36 hours;

[0076] In this embodiment, different solvents can refer to the setting method of the solvent in step (1.6).

[0077] Step (2.7): After the product in step (2.6) is dried, it is washed for 24 hours (changed to 12 hours to 36 hours), and vacuum dried again for 24 hours (changed to 12 hours to 36 hours) to obtain a covalent organic framework material-coated carbon nanotube material.

[0078] In this embodiment, the material used for washing in step (2.7) can refer to the material used for washing in step (1.7) above.

[0079] The embodiment of the present application also provides a modified electrode (i.e., a covalent organic framework material-coated carbon nanotube material modified electrode, also referred to as a COFs@MWCNTs modified electrode), the preparation method of which includes steps (3.1) to (3.3).

[0080] Step (3.1): sequentially polishing the surface of the glassy carbon electrode with Al2O3 slurry in descending order of particle size until the surface of the glassy carbon electrode has a mirror effect;

[0081] In some embodiments, in the step (3.1), the mass concentration of the Al2O3 slurry is 70-100 g / L, and the particle size in the step (3.1) is in the range of 20 nm to 2 μm.

[0082] In some embodiments, in the step (3.1), the polishing step includes: first, polishing the surface of the glassy carbon electrode 250 times with Al2O3 slurry with a particle size of 0.2μm to 2μm, and then polishing the surface of the glassy carbon electrode 250 times with Al2O3 slurry with a particle size of 30 to 50nm.

[0083] Step (3.2): ultrasonically clean the glassy carbon electrode polished in step (3.1) in water and then in anhydrous ethanol, and then blow dry in a protective atmosphere;

[0084] In some embodiments, in the step (3.2), the frequency of the ultrasonic cleaning is 30 to 50 kHz, the power is 160 to 180 W, and the time is 10 to 15 seconds.

[0085] In some embodiments, in step (3.2), the protective atmosphere comprises nitrogen or argon. The protective atmosphere used is a high-purity atmosphere with a purity of ≥99.9%.

[0086] Step (3.3): evenly drop-coat the perfluorosulfonic acid resin dispersion of the covalent organic framework material-coated carbon nanotube material on the surface of the glassy carbon electrode dried in step (3.2), and air-dry naturally to obtain the covalent organic framework material-coated carbon nanotube material modified electrode.

[0087] In some embodiments, in the step (3.3), the concentration of the perfluorosulfonic acid resin dispersion of the covalent organic framework material-coated carbon nanotube material is 0.15-1 mg / mL.

[0088] In some embodiments, in step (3.3), the amount of the perfluorosulfonic acid resin dispersion drop coating of the covalent organic framework material coated carbon nanotube material is 0.25 to 0.75 μL / mm 2 The electrode surface was modified by coating the dispersed droplets of perfluorosulfonic acid resin coated with covalent organic framework material and carbon nanotube material, and it was used as a new generation of electrode material for the determination of trace lead ion concentration.

[0089] In some embodiments, in step (3.3), the perfluorosulfonic acid resin dispersion of the covalent organic framework-coated carbon nanotube material is prepared by adding the covalent organic framework-coated carbon nanotube material to a perfluorosulfonic acid resin aqueous solution and ultrasonically dispersing the dispersion. In some embodiments, the mass volume ratio of the covalent organic framework-coated carbon nanotube material to the perfluorosulfonic acid resin aqueous solution is 0.15 to 1:1 in mg / mL. In some embodiments, the volume ratio of the perfluorosulfonic acid resin to water in the perfluorosulfonic acid resin aqueous solution is 1:8 to 10.

[0090] The embodiments of the present application also provide an electrochemical sensor (also referred to as a COFs@MWCNTs sensor), comprising the modified electrode.

[0091] An embodiment of the present application also provides an application of an electrochemical sensor, which is used for detecting heavy metal lead, including detecting heavy metal lead in electronic cigarette samples, detecting heavy metal lead in natural water bodies, and the like.

[0092] In the embodiments of the present application, as an alternative method, electrochemical sensing technology has the advantages of high cost-effectiveness, fast speed, and simple operation, and is very suitable for the rapid detection of heavy metal lead in electronic cigarette aerosols. The high porosity and ordered mesoporous structure of COFs (covalent organic frameworks) give it a large specific surface area, which can provide more active sites. MWCNTs (multi-walled carbon nanotubes) have good electrical conductivity under most environments and can withstand the erosion of strong acids, strong bases and oxidants. Therefore, COFs and MWCNTs are compounded to form COFs@MWCNTs materials, which are modified on the surface of the sensor. This can not only increase the specific surface area of ​​the sensor and enhance the electrochemical stability of the sensor, but also show the advantages of high sensitivity and low detection limit when detecting heavy metal ions. In addition, the preparation process is simple and the cost is low, and it has significant prospects for promotion and application.

[0093] In some embodiments, the application method includes steps (4.1) to (4.2).

[0094] Step (4.1): drawing a standard curve, which includes: adding a lead standard solution dropwise to the electrolyte according to a lead ion concentration gradient range of 0.1 μg / L to 200 μg / L in the electrolyte, and using an electrochemical sensor to establish a lead ion concentration and peak current standard curve using square wave anodic stripping voltammetry; wherein, if the sample to be tested is an acidic lead-containing sample solution, the pH value of the electrolyte is adjusted to 3.5-5.5 before establishing the lead ion concentration and peak current standard curve; if the sample to be tested is a weak acid or neutral lead-containing sample solution, the lead ion concentration and peak current standard curve is directly established without adjusting the pH value of the electrolyte.

[0095] In some embodiments, in the step (4.1), the concentration of the lead standard solution is 10 to 500 μg / mL.

[0096] In some embodiments, in step (4.1), the volume ratio of the electrolyte to the lead standard solution is 50 mL: 2 μL to 100 μL.

[0097] In some embodiments, in step (4.1), the electrolyte is an acetic acid-sodium acetate aqueous solution. The electrolyte has two functions: 1) as a conductive medium to transmit current; and 2) to carry out electrochemical reactions under the action of the electric field, allowing the anodic dissolution to proceed smoothly and in a controlled manner.

[0098] In some embodiments, in step (4.1), the mixed concentration of the acetic acid-sodium acetate aqueous solution is 0.05-0.15 mol / L, and the pH value is 4-5.5. When the pH value is lower than 4, H + It will compete with heavy metal ions for binding sites, resulting in a decrease in current. When the pH is higher than 4, Pb 2+It is easy to hydrolyze to produce oxides, which reduces the signal of its dissolution peak.

[0099] In some embodiments, in step (4.1), the pH value of the weak acid or neutral lead-containing sample solution is 4.5 to 8.0. The weak acid or neutral heavy metal ion-containing sample solution includes natural water, etc.

[0100] In some embodiments, in step (4.1), the pH value of the acidic lead-containing sample solution is less than 4.5. The acidic heavy metal ion-containing sample solution includes a digestion solution, etc.

[0101] In some embodiments, in step (4.1), the volume ratio of the electrolyte to the acidic lead sample solution is 50 mL:2 μL-100 μL. The pH value is adjusted to 3.5-4.5 with 5-10 mol / L acetic acid. The method of the present invention is based on a degree of fit of 0.1-200 μg / L.

[0102] In some embodiments, in the step (4.1), the electrochemical workstation model is RST5000; and the internal solution of the reference electrode Ag / AgCl is a saturated KCl solution.

[0103] Step (4.2): Step (4.2): Detection of the lead ion content in the sample to be tested, the detection of the lead ion content in the sample to be tested comprising: adding the sample to be tested into an electrolytic cell, using an electrochemical sensor, and employing square wave anodic stripping voltammetry to detect the lead ion content in the sample to be tested.

[0104] In some embodiments, in the step (4.2), the detection parameters of the square wave anodic stripping voltammetry are: enrichment potential: -0.9~-1.3V, enrichment time: 60~360s, standing time: 5~20s, starting potential: -1.3~-1.0V, ending potential: 0.2~0.6V, square wave amplitude: 0.02~0.03V, potential increment: 0.002~0.005V, square wave frequency: 20~30Hz.

[0105] In the examples of this application, the synthesized COFs@MWCNTs have good conductivity and a large number of binding sites. In addition, the COFs@MWCNTs sensor showed excellent repeatability, reproducibility and stability in the performance test. 2+ It has good electrochemical response, showing advantages such as high sensitivity, low background current and high selectivity. 2+The detection limit reached 0.0749 μg / L, and the average recovery rate was 102.28-106.75%, demonstrating a higher sensitivity of 0.221 μA / (μg / L) than the existing technology. This indicates that COFs@MWCNTs modified electrodes provide a new path for the rapid detection of trace heavy metal ions in e-cigarette liquids.

[0106] Example 1 A nanotube material

[0107] (1) A method for preparing a nanotube material comprises the following steps:

[0108] (4.1) Place 1 ml of 1,4-dioxane and 1 ml of mesitylene in an ampoule, then add 20 mg of multi-walled carbon nanotubes to the ampoule and perform the first ultrasonic treatment for 30 min.

[0109] (4.2) Add 26.57 mg of 5,5'-diamino-2,2'-bipyridine to the ampoule in step (4.1) and continue sonication for a second time for 15 min;

[0110] (4.3) Add 20 mg of 2,4,6-triformylphloroglucinol and acetic acid to the ampoule in step (4.2) and perform a third ultrasonic treatment for 10 min;

[0111] (4.4) The product in the ampoule of (4.3) after sonication was subjected to a three-step cycle of cold-freeze-thaw for 3 times;

[0112] (4.5) Evacuate the ampoule from step (4.4) and seal it with an oxyhydrogen welder; place the ampoule in a 150°C oven for two days;

[0113] (4.6) After the product in step (4.5) has cooled to room temperature, it is taken out, washed with methanol, water, and ethanol, filtered, and vacuum dried for 24 hours;

[0114] (4.7) After the product in step (4.6) is dried, it is washed with a Soxhlet extractor for 24 hours and vacuum dried again for 24 hours.

[0115] (2) Another method for preparing a nanotube material comprises the following steps:

[0116] (5.1) Place 1 ml of 1,4-dioxane and 1 ml of mesitylene in a Schlenk flask. Then add 26.57 mg of 5,5'-diamino-2,2'-bipyridine and stir for 20 min.

[0117] (5.2) Add 20 mg of multi-walled carbon nanotubes to the schlenk flask in step (5.1) and sonicate for 30 minutes;

[0118] (5.3) Add 20 mg of 2,4,6-triformylphloroglucinol and acetic acid to the Schlenk flask in step (5.2) and stir for 30 minutes;

[0119] (5.4) The stirred product in the Schlenk flask (5.3) was subjected to a three-step freeze-thaw cycle three times;

[0120] (5.5) Place the Schlenk flask in step (5.4) in a 120°C oven for 72 hours;

[0121] (5.6) After the product in step (5.5) has cooled to room temperature, it is taken out, washed with methanol, water, and ethanol, filtered, and vacuum dried for 24 hours;

[0122] (5.7) After the product in step (5.6) is dried, it is washed with a Soxhlet extractor for 24 hours and vacuum dried again for 24 hours.

[0123] (3) Characterization of nanotube materials

[0124] Figure 1 (a) is a high-resolution transmission electron microscopy (HRTEM) image of multi-walled carbon nanotubes (MWCNTs), (b)-(c) are high-resolution transmission electron microscopy (HRTEM) images of covalent organic framework materials coated with carbon nanotubes at two different magnifications; (d) is a high-angle annular dark field (HAADF) image of covalent organic framework materials coated with carbon nanotubes; (e)-(g) are elemental maps of C, N and O drawn using electron energy loss spectroscopy (EELS).

[0125] HRTEM analysis showed that Figure 1 a shows the unique tubular structure of MWCNTs (multi-walled carbon nanotubes), where the MWCNTs are well dispersed and not coated by COFs (covalent organic frameworks). Figure 1 b shows the composite structure formed by the combination of MWCNTs and COFs, showing obvious MWCNTs bundling and COFs filling phenomena. Figure 1 b The upper right corner shows an image of 50nm COFs wrapped MWCNTs, which clearly shows the ordered porous structure of COF and further verifies the crystalline nature of the material. Figure 1 c accurately measured the geometric dimensions of the nanotubes. The outer diameter of MWCNTs is 15 nm, while its outer diameter after being coated with COFs is 39 nm. This is because COFs form a uniform coating on the surface of MWCNTs, and the thickness of this coating is 12 nm. Figure 1Energy dispersive X-ray spectroscopy (EDS) images (e), (f), and (g) show the uniform distribution of carbon, oxygen, and nitrogen. The distribution of these elements plays a significant role in the detection of heavy metal ions because they provide specific functional sites for capturing and identifying heavy metal ions.

[0126] Further analysis of COFs@MWCNTs by XPS Figure 2 The XPS spectrum of a proves the presence of carbon, nitrogen and oxygen elements in COFs@MWCNTs materials. Figure 2 The high-resolution spectrum of the C1s region in (b) shows different states of carbon. The peak at 284.8 eV is due to C=C bonds between carbon atoms. Other peaks at higher binding energies indicate chemical bonds between carbon and elements such as oxygen or nitrogen, consistent with the C=N bonds in the TP-BPY-COF structure. Figure 2 The high-resolution spectrum of the N1s region in c shows peaks at 399.8 eV and 401.2 eV representing CN and C=N bonds, respectively, which are typical peaks of COFs@MWCNTs and reflect the specific structure of TP-BPY-COFs. Figure 2 The high-resolution spectrum in the O1s region (d) reveals two major peaks at 531.7 eV and 532.3 eV, respectively, indicating that oxygen atoms exist in different chemical states. These peaks are associated with the C=O and C-OH functional groups in COFs@MWCNTs, which may participate in interactions with heavy metal ions and act as coordination sites. XPS analysis of the different chemical states of COFs@MWCNTs indicates that this COF structure, linked by C=N bonds, may have high sensitivity and specificity for the detection of heavy metal ions. The presence of nitrogen and oxygen functional groups provides a large number of coordination sites for heavy metal ions, resulting in good sensitivity and stability in the detection of heavy metal ions.

[0127] Example 2 Application of the nanotube material prepared in Example 1

[0128] (I) Preparation of Covalent Organic Framework-Coated Carbon Nanotube Modified Electrodes (6.1) Polish the surface of a glassy carbon electrode 250 times with a 0.5 μm Al2O3 slurry. Then, polish the surface of a glassy carbon electrode 250 times with a 50 nm Al2O3 slurry until the electrode surface has a mirror finish.

[0129] (6.2) Ultrasonic clean the glassy carbon electrode polished in step (6.1) in deionized water and anhydrous ethanol for 10 seconds each, and blow clean the electrode surface with high-purity nitrogen gas;

[0130] (6.3) Evenly coat 5 μL of the perfluorosulfonic acid resin dispersion (0.5 mg / mL) of COFs@MWCNTs obtained in Example 1 of the preparation method of COFs@MWCNTs on the surface of the glassy carbon electrode after drying in step (6.2), and air-dry naturally to obtain a COFs@MWCNTs modified electrode.

[0131] The preparation method of the perfluorosulfonic acid resin dispersion of COFs@MWCNTs in (6.3) is as follows: 0.5 mg of COFs@MWCNTs obtained in Example 1 of the preparation method of COFs@MWCNTs is added to 1 mL of perfluorosulfonic acid resin aqueous solution (the volume ratio of perfluorosulfonic acid resin: water is 1:9) and ultrasonically dispersed for 20 minutes.

[0132] (2) Establishment of standard curve for heavy metal lead detection

[0133] (1) The lead standard solution was added dropwise to 50 mL of acetic acid-sodium acetate aqueous solution (0.1 mol / L, pH 4) in the electrolytic cell, so that after each addition, the Pb content in the electrolytic cell solution was 2+ The concentrations were: 0, 0.1, 0.3, 0.8, 1.5, 3, 5, 10, 30, 50, 70, 100, 150, 200 μg / L, and then the COFs@MWCNTs modified electrode obtained in Example 1 of the preparation method of the COFs@MWCNTs modified electrode was used as a working electrode, Ag / AgCl (the internal solution was a saturated KCl solution) as a reference electrode, and a Pt wire as a counter electrode were connected to the electrochemical workstation RST5000.

[0134] (2) Under stirring conditions at a speed of 300 r / min, square wave anodic stripping voltammetry was used to detect the Pb 2+ Content (detection parameters: enrichment potential: -1.1V, enrichment time: 240s, standing time: 10s, starting potential: -1.1V, ending potential: 0.4V, square wave amplitude: 0.025V, potential increment: 0.004V, square wave frequency: 25Hz).

[0135] like Figure 3 As shown, [Pb 2+ (0.1~200μg / L) The current-potential curve clearly shows that as the lead ion concentration increases from 0.1ppb to 200ppb, the dissolution peak current value increases significantly, and the dissolution peak potential gradually shifts to the positive direction with the increase in concentration. This is because it may be related to the adsorbate. When the peak current increases to 200μg / L, Pb 2+ The peak current reaches the maximum value because Pb 2+The adsorption reaches saturation, and the peak current no longer increases. The linear relationship is further confirmed by the inset in the upper right corner, which shows the proportional relationship between the peak current and the lead ion concentration. The linear regression equation is y = 0.221x - 1.254, with a goodness-of-fit R² = 0.995, highlighting the excellent performance of the sensor from low to very high concentrations. The limit of detection (LOD) is calculated as 0.074 μg / L using the formula LOD = 3 × σ / S (σ is the relative standard deviation of the background current, and S is the slope of the calibration curve). The sensitivity is 0.221 μA / (μg / L), which is far below the maximum permitted concentration for heavy metal ion detection established by the World Health Organization (Pb: 50 μg / L). The COFs@MWCNTs electrochemical sensor demonstrates high sensitivity and a wide detection range for lead ion detection. Its low limit of detection (LOD) of 0.074 ppb holds great potential for heavy metal ion monitoring. Furthermore, the sensor is low-cost and environmentally friendly, making it a significant advantage in practical applications.

[0136] (III) Detection of heavy metal lead using COFs@MWCNTs modified electrodes (actual sample detection)

[0137] Pb in electronic cigarette digestion solution 2+ To test, the e-cigarette liquid was digested. To prepare the e-cigarette digestion solution, first weigh 0.3-0.4g of e-cigarette liquid and place it in a polytetrafluoroethylene tank. At the same time, prepare a blank sample and add 5mL of nitric acid and 2mL of hydrogen peroxide. Follow the digestion program set by the microwave digestion conditions in the standard and program the temperature to react. Remove the digestion tube and transfer the digestion solution to a 50mL reagent bottle. Wash the inner tank with water three times, combine the washing solution and adjust the volume to the scale. After mixing, test the solution on the instrument according to the GB5009.11-2014 instrument conditions. Different concentrations of Pb were prepared respectively. 2+ The solution recorded the Pb content in the e-cigarette digestion solution by electrochemical method. 2+ Response. Figure 4 As shown in ab, with Pb 2+ As the concentration increases, the corresponding potential peak increases significantly near -0.6V. According to the standard curve, the Pb content in electronic cigarettes is simulated. 2+ The calculated concentrations were 7.11 μg / L and 12.03 μg / L. In addition to the quantitative analysis of the electronic cigarette digestion liquid sample according to the method of detecting heavy metals using COFs@MWCNTs modified electrodes in Example 1, an inductively coupled plasma mass spectrometer (ICP-MS) was used as a verification method to detect Pb 2+ The electronic cigarette modified electrode detection method is as follows: the electronic cigarette digestion solution in this example is diluted 250 times with 0.1 mol / L HAc-NaAc and then tested. The test results are shown in Table 1.

[0138] Table 1 Detection of Pb in electronic cigarette digestion solution using COFs@MWCNTs modified electrodes 2+ The measured value, recovery rate and ICP-MS results

[0139]

[0140] Note: The calculation formula of recovery rate in the table is (three parallel measurements of Pb 2+ Average content) / Pb 2+ concentration.

[0141] From Table 1, we can see that in Pb 2+ In the concentration range of 0 to 20 μg / L, Pb 2+ The recovery rate was 100.25-101.57%, which proved that COFs@MWCNTs modified electrodes showed good performance in electronic cigarette detection and could detect Pb in a complex environmental system. 2+ It also has good selectivity, and it is proved that the modified electrode has good stability, anti-interference and accuracy when used in practical environments.

[0142] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application. The above is only a preferred embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application. These improvements and variations should also be regarded as the scope of protection of the present application.

Claims

1. A nanotube material, characterized in that: The preparation method thereof comprises: Step (1.1): subjecting the solvent of 1,4-dioxane, mesitylene and multi-walled carbon nanotubes to a first ultrasonic treatment; Step (1.2): adding 5,5'-diamino-2,2'-bipyridine to the material obtained after the first ultrasonic treatment and continuing the second ultrasonic treatment; Step (1.3): adding 2,4,6-triformylphloroglucinol and acetic acid to the substance obtained after the second ultrasonic treatment, and performing a third ultrasonic treatment; Step (1.4): subjecting the material after the third ultrasonic treatment to a three-step cold-freeze-thaw cycle for multiple times; Step (1.5): subjecting the product in step (1.4) to a solvothermal reaction under vacuum conditions; Step (1.6): After the product in step (1.5) is cooled to room temperature, it is taken out, washed with different solvents, filtered, and vacuum dried; Step (1.7): After the product in step (1.6) is dried, it is washed and vacuum dried again to obtain a covalent organic framework material coated with a carbon nanotube material.

2. The nanotube material according to claim 1, characterized in that: The volume ratio of 1,4-dioxane to mesitylene is 1:1; the mass ratio of the multi-walled carbon nanotubes to 2,4,6-triformylphloroglucinol is 1:

1.

3. The nanotube material according to claim 1, characterized in that: The mass ratio of the 5,5'-diamino-2,2'-bipyridine to 2,4,6-triformylphloroglucinol is 3:

4.

4. The nanotube material according to claim 1, characterized in that: The mass ratio of the 2,4,6-triformylphloroglucinol to 5,5'-diamino-2,2'-bipyridine is 4:3, and the volume ratio of the acetic acid to 1,4-dioxane is 2:

1.

5. The nanotube material according to claim 1, characterized in that: The steps of the cold-freeze-thaw three-step method include: freezing the material after the third ultrasonic treatment in step (1.3) until it is completely solidified in liquid nitrogen, evacuating it under a vacuum pump with a vacuum degree of -0.5 to 0 MPa, thawing it in a water bath at 25°C to 45°C and filling it with nitrogen.

6. A nanotube material, characterized in that: The preparation method thereof comprises: Step (2.1): stirring a solvent of 1,4-dioxane, mesitylene and 5,5'-diamino-2,2'-bipyridine; Step (2.2): adding multi-walled carbon nanotubes to the product of step (2.1) and subjecting to ultrasonic treatment; Step (2.3): adding 2,4,6-triformylphloroglucinol and acetic acid to the substance obtained after ultrasonic treatment, and stirring; Step (2.4): subjecting the product of step (2.3) to a three-step cold-freeze-thaw cycle for multiple times; Step (2.5): subjecting the product in step (2.4) to a solvothermal reaction; Step (2.6): After the product in step (2.5) is cooled to room temperature, it is taken out, washed with different solvents, filtered, and vacuum dried; Step (2.7): After the product in step (2.6) is dried, it is washed and vacuum dried again to obtain a covalent organic framework material coated with a carbon nanotube material.

7. A modified electrode, characterized in that: The preparation method thereof comprises: Step (3.1): polishing the surface of the glassy carbon electrode in order of decreasing particle size with Al2O3 slurry until the surface of the glassy carbon electrode presents a mirror effect; Step (3.2): ultrasonically clean the glassy carbon electrode polished in step (3.1) in water and then in anhydrous ethanol, and then blow dry in a protective atmosphere; Step (3.3): Evenly drop-coat the surface of the glassy carbon electrode dried in step (3.2) with a perfluorosulfonic acid resin dispersion of a covalent organic framework material-coated carbon nanotube material, and air-dry naturally to obtain a covalent organic framework material-coated carbon nanotube material modified electrode.

8. An electrochemical sensor, characterized in that The method comprises applying the modified electrode according to claim 7.

9. An application of an electrochemical sensor, characterized in that: The electrochemical sensor described in claim 8 is used for detecting heavy metal lead.

10. The application according to claim 9, wherein the application method comprises: Step (4.1): Drawing a standard curve, the drawing of the standard curve comprising: adding a lead standard solution dropwise into the electrolyte according to a lead ion concentration gradient range of 0.1 μg / L to 200 μg / L in the electrolyte, using an electrochemical sensor and a square wave anodic stripping voltammetry to establish a lead ion concentration and peak current standard curve; wherein, if the sample to be tested is an acidic lead-containing sample solution, the pH value of the electrolyte is adjusted to 3.5-5.5 before establishing the lead ion concentration and peak current standard curve; Step (4.2): Detection of the lead ion content in the sample to be tested, the detection of the lead ion content in the sample to be tested comprises: adding the sample to be tested into an electrolytic cell, using an electrochemical sensor, and adopting square wave anodic stripping voltammetry to detect the lead ion content in the sample to be tested.